Dijkstra’s algorithm in Product Searching System (ProSearch) / Nur Hasni Nasrudin ... [et al.] - Nasrudin, Nur Hasni; Nasaruddin, Siti Hajar; Syed Abdul Halim, Syarifah Syafiqah Wafa; Ahmad Junid, Rosida (2015)
There are huge numbers of supermarkets these days. Some customers find it difficult for them to get the items that are needed for. Customers need to search every-where in the supermarket to find the product without knowing the exact location and availability. Preliminary study had been conducted in one popular supermarket in Perak. There were 30 respondents participated in the survey and had to respond to four (4) main questions; a) Searching duration, b) Emotional Impact, c) Supermarket staffs’ assistance, d) Proposing a System Application as a solution. The results from the survey have led to the development of ProSearch application system. ProSearch is a system that is developed by applying a graph search algorithm called Dijkstra Algorithm so as to find and identify the shortest path to reach the product. Dijkstra algorithm is able to solve the single-source shortest path problems. It has been used in game development and Geographic Information Systems (GIS) application. ProSearch enable user to identify the location of the product in a supermarket. To avoid from making mistakes ProSearch offer facilities to dis-play the product picture and availability status to the user. ProSearch has been tested in three different browsers; Internet Explorer, Chrome and Firefox. It was found that Chrome browser is the most compatible browser and it has the fastest loading time. ProSearch then has been tested in one popular supermarket. However, surprisingly the management refused to implement ProSearch due to some reasons that will be discussed later in this paper.